2022
DOI: 10.1016/j.heliyon.2022.e08796
|View full text |Cite|
|
Sign up to set email alerts
|

Scaffolds of bioactive glass (Bioglass®) combined with recombinant human bone morphogenetic protein -9 (rhBMP-9) for tooth extraction site preservation

Abstract: The study aimed to investigate the osteogenic ability of bioactive glass (bioglass) combined with recombinant human bone morphogenetic protein-9 (rhBMP-9) on rat bone marrow mesenchymal stem cells (BMSCs) in vitro. The study also compares bone regeneration using rhBMP9 soaked with different carrier systems, including bioglass or collagen membranes (BioGide, BG) in a rat alveolar bone site preservation model in vivo. Methods: Scanning electron microscopy was employed to analyze bioglass surface. The absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…On the other hand, various BAG composites have been investigated for use in specialties dealing with bone graftings/tissue engineering, such as orthopedics and dentistry. For example, Shi et al (17) combined the recombinant human bone morphogenetic protein-9 (rhBMP-9) with carriers such as BAG and collagen membranes (BioGide) to utilize in the preservation of tooth extraction site in a very recently published study, and they found a dramatic difference between BAG and BioGide regarding absorption and slow/steady release of rhBMP-9. Another composite of BAG is prepared with chitosan-alginate.…”
Section: Summary Of Histopathological Examination Resultsmentioning
confidence: 99%
“…On the other hand, various BAG composites have been investigated for use in specialties dealing with bone graftings/tissue engineering, such as orthopedics and dentistry. For example, Shi et al (17) combined the recombinant human bone morphogenetic protein-9 (rhBMP-9) with carriers such as BAG and collagen membranes (BioGide) to utilize in the preservation of tooth extraction site in a very recently published study, and they found a dramatic difference between BAG and BioGide regarding absorption and slow/steady release of rhBMP-9. Another composite of BAG is prepared with chitosan-alginate.…”
Section: Summary Of Histopathological Examination Resultsmentioning
confidence: 99%
“…Rat dental follicle stem cells transduced by BMP-9 displayed enhanced alkaline phosphatase activity, mineralization, and expression of bone-related genes in a previous three-dimensional cell culture investigation ( DLX5 , OPN , Osx , and RUNX2 ) [ 44 ]. The BMP-9 dosage varied in various experimental contexts [ 13 , 45 , 46 , 47 ]. A low dose of 1 ng/mL of BMP-9 was used to treat the cells.…”
Section: Discussionmentioning
confidence: 99%
“…BMP-9 is a powerful synergist for hematopoietic progenitor cell proliferation and colony formation, and it may play a role in the establishment and maintenance of neuronal cholinergic phenotypes in the Medicina 2023, 59, 1315 2 of 12 central nervous system [12]. Recombinant human BMP-9 has been used in an animal model along with bioactive glass scaffolds to preserve the extraction site of teeth [13]. In recent studies, the strong osteogenic capacity of human dental MSCs stimulated with BMP-9 was demonstrated both in vivo and in vitro [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In cases of critical size defects, osteocunductive factors are particularly important. In the injured bone, GFs have been incorporated using a variety of approaches [ 74 ]. GF-loaded Ca-P coatings have been widely applied to orthopedic and craniofacial implants made from collagen [ 75 ].…”
Section: Conventional Drug-eluting Implantsmentioning
confidence: 99%